Enhancing upconversion luminescence by annealing processes and the high-temperature sensing of ZnO:Yb/Tm nanoparticles. (26th June 2017) - Li, Yuemei; Li, Yongmei; Wang, Rui; Xu, Yanling; Zheng, Wei
Abstract : Temperature that affects upconversion luminescence (UCL) is important to biological sensing and magnetic imaging. Abstract : Temperature that affects upconversion luminescence (UCL) is important to biological sensing and magnetic imaging. The temperature-dependent UCL of ZnO:Yb 3+ /Tm 3+ nanoparticles (UCNP) was characterized. A detailed analysis of UCL spectra at different annealing temperatures revealed the effects of annealing temperatures, which were determined by using TGA. The blue and the red UCL emissions under NIR 980 nm excitation were greatly enhanced with the increase of annealing temperature from 300 to 780 °C. The change in high-frequency groups (OH − and CO3 2− ) at different annealing temperatures were investigated using IR technique. It was found that the quenching centers were removed due to an increase of annealing temperature. Moreover, for the temperature range of 293 to 338 K, the thermal sensor based on the position shift of the 475 nm wavelength was studied. In addition, relative sensor sensitivity reached a maximum of 2.1% K −1 at 293 K based on the temperature-dependent fluorescence intensity ratio (FIR) of the 700 and 800 nm upconverted emission, which would make the ZnO:Yb 3+ /Tm 3+ nanoparticles a promising candidate for the biological temperature probe.